2001
DOI: 10.1159/000047686
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cerebral Small Vessel Disease by Proton Spectroscopy and Morphological Magnetic Resonance

Abstract: This study sought to investigate whether clinical and neuropsychological impairment in cerebral small vessel disease (CSVD) can be evaluated by proton spectroscopy (1H-MRS) and structural magnetic resonance (MR) imaging. Sixteen patients with CSVD and 15 healthy age-matched controls participated in the study. In addition to spectroscopic and structural MR examination all patients underwent a comprehensive clinical and neuropsychological investigation. Significant differences in between patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…12 The NAA/Cr ratio also correlates with cerebral oxygen metabolism of the gray matter in patients with steno-occlusive carotid artery disease. 16 In addition, a decrease in the NAA/Cr ratio is associated with a decrease in cognitive function in elderly populations, 18,21 patients with cerebral infarction, 17,22 and those with Alzheimer disease. 20 Thus, the present data suggested that neuronal damage caused by CEA results in postoperative cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 The NAA/Cr ratio also correlates with cerebral oxygen metabolism of the gray matter in patients with steno-occlusive carotid artery disease. 16 In addition, a decrease in the NAA/Cr ratio is associated with a decrease in cognitive function in elderly populations, 18,21 patients with cerebral infarction, 17,22 and those with Alzheimer disease. 20 Thus, the present data suggested that neuronal damage caused by CEA results in postoperative cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…13 On the basis of these hypotheses, proton MR spectroscopy has been applied for the study of various pathologic conditions of the cen-tral nervous system. 11,12,[14][15][16][17][18][19][20][21][22] Several studies have also investigated relative changes in NAA and/or choline following CEA by using proton MR spectroscopy. [23][24][25][26] However, the clinical significance of such postoperative changes remains unknown.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria were: (1) stroke history with full clinical recovery 15 and normal electromyogram recordings from 2 hand muscles (M. flexor pollicis longus, M. extensor digitorum communis); (2) brain infarction of, at least, the frontal lobe without hemorrhage; (3) no macroscopic lesion of the hand representation in primary sensorimotor cortex, SMA, CRB, basal ganglia, or thalamus on 3-dimensional (3D) T1-weighted images; (4) no severe cerebral small-vessels disease on T2-weighted images defined by a score Ͼ12 based on MR structural abnormalities; 16 and (5) no significant cerebrovascular stenosis (Ն70% based on NASCET measurement) assessed by Doppler and duplex sonography. Exclusion criteria of the study were: (1) excessive blood pressure Ͼ140/90 mm Hg at the time of examination; (2) tachycardia (pulse Ͼ120/min); (3) hypoxemia (PaO 2 Ͻ90 mm Hg); and (4) inappropriate task performance (see HV subsection).…”
Section: Subjectsmentioning
confidence: 99%
“…Acute demyelination has been associated with an increase in choline levels (13), which reflect cholinecontaining compounds that are involved in membrane synthesis and degradation. Previous studies in patients with cerebral SVD have shown reductions in NAA and choline in lesions and normal appearing white matter, compared with controls (14,15). In order to shed light on the pathological basis of the imaging abnormalities noted on DTI in SVD, we investigated the relationship between DTI parameters and metabolite concentration ratios obtained at the same MRI examination.…”
Section: Introductionmentioning
confidence: 99%